2012
DOI: 10.1089/bfm.2011.0029
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Breastmilk Expression by 1 Month Postpartum and Influence on Breastmilk Feeding Duration

Abstract: Breastmilk expression in this cohort was common even within the first month postpartum before mothers in the United States typically go back to work. "Breastfeeding" classification needs to be updated to include options for breastmilk expression so the appropriate study of health outcomes related to this practice can be determined.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
28
1
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(33 citation statements)
references
References 24 publications
3
28
1
1
Order By: Relevance
“…This suggests many women were likely replacing a portion of at-breast feeds with expressed milk beginning shortly after birth (confirmed by participants’ open-ended responses regarding reasons for milk expression at the two-week interview). Our data are consistent with a prospective cohort study in the U.S., which found that 75% (n=18/24) of primiparous women had expressed milk by four weeks postpartum (Geraghty, Davidson, Tabangin, & Morrow, 2012). …”
Section: Discussionsupporting
confidence: 91%
“…This suggests many women were likely replacing a portion of at-breast feeds with expressed milk beginning shortly after birth (confirmed by participants’ open-ended responses regarding reasons for milk expression at the two-week interview). Our data are consistent with a prospective cohort study in the U.S., which found that 75% (n=18/24) of primiparous women had expressed milk by four weeks postpartum (Geraghty, Davidson, Tabangin, & Morrow, 2012). …”
Section: Discussionsupporting
confidence: 91%
“…Expressing milk by 4 weeks postpartum was not associated with duration of breastfeeding or provision of breastmilk. 11 In a study of 946 women in the Midwest region of the United States, Schwartz et al 12 found that the use of breast pumps in the first 3 weeks postpartum put women at a higher risk for cessation of breastfeeding, even when controlling for pain and mastitis. In contrast, after 3 weeks, the use of manual expression reduced the risks of early weaning.…”
Section: Effect Of Breast Pumps On Initiation and Duration Of Lactationmentioning
confidence: 99%
“…Pumping in the first month does not have a significant influence on breastfeeding duration. 58 However, pumping in the first 6 months is associated with longer breastfeeding duration, while pumping at 3 days postpartum is associated with shorter breastfeeding duration. 50 Furthermore, one study found that expressing breast milk (defined as either use of a mechanical pump or hand expression) in the first three weeks was associated with breastfeeding discontinuation by 3 months of age.…”
Section: Mother’s Experiences Of Milk Expressionmentioning
confidence: 99%